Microstructure and Wear Properties of Hot-Pressed NiCrBSi/TiC Composite Materials - Islak, S.; Ulutan, M.; Buytoz, S. (Pleiades Publishing Ltd, 2020)
In this study, TiC-reinforced NiCrBSi matrix composite materials were produced using the hot pressing powder metallurgy (PM) technique. The effect of the addition of titanium carbide to NiCrBSi powder in different proportions (5, 10, and 20 wt %) on the microstructure, hardness, relative density, and wear properties of composites was investigated experimentally. NiCrBSi-TiC composites were produced for 10 min at 1000 degrees C with an applied pressure of 45 MPa using a vacuum-assisted automatic hot-pressing machine. The wear behaviors of the composites were compared through dry sliding wear tests. Wear rates and coefficient of friction (COF) values were observed of composites. In addition, the main wear mechanisms are investigated by using SEM and EDS analyses of the worn surfaces. The wear rates of the composites were decreased by increasing the TiC content.
Keywords: NiCrBSi; titanium carbide; friction; metal-matrix composites (MMCs); wear